UMP Foundation, volunteers give aid to flood victims - Siti Nur Azwin, Zulkapri (The New Straits Times Press (M) Bhd., 2021)
KUANTAN: To ease the burden of flood victims in Pahang, Universiti Malaysia Pahang (UMP) Foundation, along with their team of volunteers, have been going to the ground to provide various forms of assistance.